Islamic Consumption Principle And Religiosity Toward Muslim Community Consumption Behavior - Putriana Putriana (LPPM ISNJ Bengkalis, 2023)
Islamic consumption behavior must reflect a Muslim's closeness to Allah, obtained in the right way, reasonable, transparent, not wasteful, not redundant, not excessive, and there are limits on consumption. For this reason, Muslims in consuming must comply with the rules of Islamic teachings. This study aims to analyze and demonstrate the effect of Islamic consumption principles and religiosity on the consumption behavior of Muslim communities. The methodology used is quantitative with the SEM-SmartPLS analysis tool. The population in this study is the entire productive Muslim community in Pekanbaru, whose exact number is unknown. The sampling technique of this study was carried out using random sampling of 107 Muslim communities. The study results show that the principle of Islamic consumption does not affect the consumption behavior of Islamic society. Religiosity positively and significantly affects the consumption behavior of the Islamic community. The principle of Islamic consumption and religiosity can simultaneously explain the consumption behavior of Muslim society by 56.7% and have a strong relationship. This research theoretically can make religiosity a theoretical basis and measure Muslim society's consumption behavior. While practically, it can be a reference in prioritizing beliefs or faith, religious practices, religious knowledge, experiences, and consequences on the consumption behavior of Muslim communities.